New data on distribution of caucasian Rhododendron (Rhododendron caucasicum Pall.) in Armenia - Asatryan, A. T. (Армянское ботаническое общество)
New population of Rhododendron caucasicum - an endangered species of Armenian flora is found on Pambak mountain range. It is stated to be the largest known population of the species in Pambak mountains. The presence of the species is confirmed at the Mountain Bazumtar (Todor) of Bazum mountain range - for the first time in the 99 years since the first record of R. caucasicum in Armenia was made from this location. Հայտնաբերվել է Հայաստանի ֆլորայի վտանգված տեսակ Rhododendron caucasicum-\] նոր պոպուլյացիւս Փամբակի լեռնաշղթայում: Այն նկարագրվում է որպես Փամբակի լեռներում տվյալ տեսակի հայտնի պոպուլյացիաներից ամենախոշորը: Առաջին անգամ, 99 տարի անց, հաստատվել է մրտավարդ կովկասյանի առկայությունը Բազումի լեռնաշղթայի Բազումթառ (Թոդոր) լեռան վրա' Հայաստանում այս տեսակի առաջին գրանցման վայրում: Новая популяция находящегося под угрозой вида флоры Армении Rhododendron caucasicum обнаружена на Памбакском хребте. Данная популяция отмечается как самая крупная из всех популяций вида известных с этого хребта. Впервые через 99 лет после первой регистрации рододендрона кавказского в Армении подтверждено присутствие вида в пункте этой находки - на горе Базумтар (Тодор) Базумского хребта.
Keywords: Բուսաբանություն